Respuesta :

Explanation:

2x+3y=11       y=x-3

2x+3(x-3)=11

2x+3x-9=11

5x=20/:5

x=4

y=x-3

y=4-3

y=1

Answer:

x=4 and y=1

Explanation:

Let's solve your system by substitution.

2x+3y=11;y=x−3

Rewrite equations:

y=x−3;2x+3y=11

Step: Solve y=x−3 for y:

y=x−3

Step: Substitute x−3 for y in 2x+3y=11:

2x+3y=11

2x+3(x−3)=11

5x−9=11 (Simplify both sides of the equation)

5x−9+9=11+9( Add 9 to both sides)

5x=20

5x/5=20/5

(Divide both sides by 5)

x=4

Step: Substitute 4 for x in y=x−3:

y=x−3

y=4−3

y=1(Simplify both sides of the equation)

Answer:

x=4 and y=1